Hepatocellular Carcinoma in Acute Hepatic Porphyrias: Results from the Longitudinal Study of the U.S. Porphyrias Consortium. Issue 5 (11th December 2020) - Saberi, Behnam; Naik, Hetanshi; Overbey, Jessica R.; Erwin, Angelika L.; Anderson, Karl E.; Bissell, D. Montgomery; Bonkovsky, Herbert L.; Phillips, John D.; Wang, Bruce; K.Singal, Ashwani; M.McGuire, Brendan; Desnick, Robert J.; et al.
Abstract : Background and Aims: The risk for hepatocellular carcinoma (HCC) is increased in acute hepatic porphyrias (AHP). The aim of this study was to explore the clinicopathologic characteristics, outcomes, and frequency of HCC in patients with AHP in the United States. Approach and Results: This cross‐sectional analysis evaluated patients with HCC in a multicenter, longitudinal study of AHP. Among 327 patients with AHP, 5 (1.5%) were diagnosed with HCC. Of the 5 HCC cases, 4 had acute intermittent porphyria and 1 had variegate porphyria, confirmed by biochemical and/or genetic testing. All patients were white females, with a median age of 27 years (range 21‐75) at diagnosis. The median age at HCC diagnosis was 69 years (range 61‐74). AHP was asymptomatic in 2 patients; 2 reported sporadic attacks; and 1 reported recurrent attacks (>4 attacks/year). All patients had a single HCC lesion on liver imaging that was 1.8‐6.5 centimeters in diameter. Serum alpha fetoprotein levels were below 10 ng/mL in all 4 patients with available results. Four patients underwent liver resection, and 1 was treated with radioembolization. No significant inflammation or fibrosis was found in adjacent liver tissues of 3 patients who underwent liver resection. Two patients developed recurrence of HCC at 22 and 26 months following liver resection. All patients are alive with survival times from HCC diagnosis ranging from 26‐153 months. Conclusion: In this U.S. study, 1.5% of patients with AHP had HCC. HCC in AHP occurred in the absence of cirrhosis, which contrasts with other chronic liver diseases. Patients with AHP, regardless of clinical attacks, should be screened for HCC, beginning at age 50. The pathogenesis of hepatocarcinogenesis in AHP is unknown and needs further investigation.